Involvement of MicroRNAs in the Aging-Related Decline of CD28 Expression by Human T Cells - Teteloshvili, Nato; Dekkema, Gerjan; Boots, Annemieke M.; Heeringa, Peter; Jellema, Pytrick; de Jong, Debora; Terpstra, Martijn; Brouwer, Elisabeth; Pawelec, Graham; Kok, Klaas; van den Berg, Anke; Kluiver, Joost; et al. (Frontiers in Immunology, 2018)
Loss of CD28 is a characteristic feature of T cell aging, but the underlying mechanisms of this loss are elusive. As differential expression of microRNAs (miRNAs) has been described between CD28+ and CD28- T cells, we hypothesized that altered miRNA expression contributes to the age-associated downregulation of CD28. To avoid the confounding effects of age-associated changes in the proportions of T cells at various differentiation stages in vivo, an experimental model system was used to study changes over time in the expression of miRNA associated with the loss of CD28 expression in monoclonal T cell populations at a lower or higher number of population doublings (PDs). This approach allows identification of age-associated miRNA expression changes in a longitudinal model. Results were validated in ex vivo samples. The cumulative number of PDs but not the age of the donor of the T cell clone correlated with decreased expression of CD28. Principal component analysis of 252 expressed miRNAs showed clustering based on low and high PDs, irrespective of the age of the clone donor. Increased expression of miR-9-5p and miR-34a-5p was seen in clones at higher PDs, and miR-9-5p expression inversely correlated with CD28 expression in ex vivo sorted T-cells from healthy subjects. We then examined the involvement of miR-9-5p, miR-34a-5p and the members of the miR-23a~24-2 cluster, which are all predicted to bind to the 3’UTR of CD28, in the IL-15-induced loss of CD28 in T cells. Culture of freshly-isolated naive CD28+ T cells in the presence of IL-15 resulted in a gradual loss of CD28 expression, while the expression of miR-9-5p, miR-34a-5p and members of the miR-23a~24-2 cluster increased. Binding of miR-9-5p, miR-34a-5p, miR-24-3p and miR-27- 3p to the 3’UTR of CD28 was studied using luciferase reporter constructs. Functional binding to the 3’UTR was shown for miR-24-3p and miR-27a-3p. Our results indicate involvement of defined miRNAs in T cells in relation to specific characteristics of T cell aging, i.e. population doubling and CD28 expression.